Decolonising Religious Studies in South Africa: Reflections on the field 26 years after democracy - Scharnick-Udemans, Lee-Shae S. (Religion compass, 2021)
In light of the decolonial turn in scholarship, this essay maps the state of the field for Religious Studies in South Africa, 26 years after the first democratic elections. It suggests that between the genealogical critique of the discipline and the mapping of decoloniality in research and teaching, a description and assessment of the institutional presence and politics of Religious Studies and theology is necessary. This conceptual pause allows us to chart the practical possibilities and limitations for the discipline's future. By highlighting the contested Christonormativity that characterises contemporary South African public culture and illustrating the overrepresentation of theology in higher education, I argue that the flourishing of Christian privilege in higher education should be more critically considered within the decolonial project.